Public Voices and Cyber Controversy: A Critical Discourse Analysis of the #Bjorka Trending Topic on Twitter (X) - Tasya Salsabilla Dirgantari; Drina Intyaswati; Utih Amartiwi (Universitas Ahmad Dahlan, 2025)
Trending topics on Twitter (X) play a significant role in highlighting public-interest issues. This study aims to examine the meanings constructed in tweets related to the trending hashtag #Bjorka on Twitter (X). A descriptive qualitative approach was employed, with data collected through textual observation, data scraping, and documentation. The analysis was conducted using Teun A. van Dijk’s critical discourse analysis model across three dimensions: text, social cognition, and social context. In the textual dimension, many tweets expressed frustration and sarcasm toward the government and police for their perceived incompetence in handling the Bjorka case. In the social cognition dimension, tweet authors interpreted that Bjorka was not an actual hacker. In the social context dimension, the public demanded accountability. This study contributes to digital discourse research by demonstrating how public narratives can shift from an initial issue to broader political criticism, underscoring the need for further research on news patterns and issue framing in shaping public discourse. The findings are expected to serve as a reference for both the public and the Indonesian government—particularly the Ministry of Communication and Digital Affairs (Komdigi), the National Cyber and Crypto Agency (BSSN), and the Indonesian National Police (Polri)—to take a more proactive role in addressing cybercrime and strengthening personal data security systems, thereby restoring public trust and preventing similar incidents in the future.